Why Median Severity and Ordinal Scale Severity Values should not be used for Injury Burden Results: A Critical Review - Fuller, Colin W (International Journal of Sports Medicine, 2023)
Injury burden is a composite measure of injury incidence and mean severity; this parameter has been reported as an output measure from injury surveillance studies in rugby for over 20 years. The benefits of reporting injury burden results have, more recently, been recognised in other sports. This wider use of injury burden as an output measure from injury surveillance studies has, however, highlighted misunderstandings about how to calculate, present and interpret injury burden data. The aim of this critical review is to explain why median severity and ordinal severity scales should not be used to calculate and report injury burden results in injury surveillance studies. Equations are presented to show how injury burden results should be calculated, and graphs and tables are presented to explain the errors that are introduced when median severity and ordinal scales of severity are used instead of mean severity. This critical review is intended to highlight the correct procedures for calculating, reporting and interpreting injury burden results in order to avoid incorrect results, conclusions and injury prevention recommendations being published.
Keywords: surveillance; risk; prevention